2015
DOI: 10.1186/s12918-015-0235-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular automaton-based model for radiation-induced bystander effects

Abstract: BackgroundThe radiation-induced bystander effect is a biological response observed in non-irradiated cells surrounding an irradiated cell. The bystander effect is known to be induced by two intercellular signaling pathways, the medium-mediated pathway (MDP) and the gap junctional pathway (GJP). To investigate the relative contribution of each signaling pathway, we have developed a mathematical model of the cellular response through these two pathways, with a particular focus on cell-cycle modification.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In addition, cells might be affected by irradiated cells in close proximity even though they were not hit themselves. Those nontargeted or bystander effects are triggered by direct cell–cell communications or the release of signal molecules [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cells might be affected by irradiated cells in close proximity even though they were not hit themselves. Those nontargeted or bystander effects are triggered by direct cell–cell communications or the release of signal molecules [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These well-documented responses are collectively known as the non-targeted radiation effects, although the underlying molecular mechanisms remain to be determined [ 1 ]. Several studies have shown significant alterations in cell survival in vitro in spatially modified radiation fields, experimentally [ 2 , 3 , 4 ] and theoretically [ 5 , 6 , 7 ]. This impact on cell survival is partially driven by intercellular signaling via gap junctions or soluble factors between irradiated cells and non-irradiated cells in living systems [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Powathil et al [10] propose a multiscale model incorporating spatiotemporal information of bystander, oxygen distribution and cell cycle phases. Cell cycle dynamics in BE signalling also has been studied by Hattori et al [11] via cellular automaton-based model. The integrated microdosimetric-kinetic model has been proposed to reveal the role of DNA repair kinetics in HRS [12].…”
Section: Introductionmentioning
confidence: 99%